Students’ Self-Awareness Profile at MTs Negeri 2 Bandung and Its Educational Implications - Rostiawan, Fitra Fajar; Barida, Muya (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2025)
Self-awareness plays a crucial role in personality development and adolescent adaptation. However, many adolescents still struggle to recognize and manage themselves effectively, which impacts various psychological dimensions. This study aims to describe the self-awareness profile of students at MTs Negeri 2 Bandung. Using a quantitative descriptive approach, the study involved a population of 200 students, with 127 selected through purposive sampling. Data were analyzed descriptively to determine frequency distributions and percentages across self-awareness categories. The findings show that 42.5% of students possess moderate self-awareness, 25% fall into the low category, and 6% belong to the very low category. The action and conversation dimensions dominate the moderate category, with 43.3% and 40.9%, respectively. To enhance students’ self-awareness, several guidance and counseling interventions are recommended, including self-monitoring, cognitive restructuring, role-playing, mindfulness practices, and psychoeducation, all of which can contribute to students’ personal development.